Incorporating equity issues into the development of Colombian clinical practice guidelines: suggestions for the GRADE approach (2016)
Objective To propose how to incorporate equity issues, using the GRADE approach, into the development and implementation of Colombian Clinical Practice Guidelines.Methodology This proposal was developed in four phases: 1. Included a literature review and the development of a preliminary proposal about how to include equity issues; 2. Involved an informal discussion to reach a consensus on improving the first proposal; 3. Was a survey of the researchers’ acceptance levels of the proposal, and; 4. A final informal consensus was formed to adjust the proposal.Results A proposal on how to incorporate equity issues into the GRADE approach was developed. It places particular emphasis on the recognition of disadvantaged populations in the development and implementation of the suggested guideline. PROGRESS-Plus is recommended for use in exploring the various categories of disadvantaged people. The proposal suggests that evidence be rated differentially by giving higher ratings to studies that consider equity issues than those that do not. The proposal also suggests the inclusion of indicators to monitor the impacts of the implementation of CPGs on disadvantaged people.Conclusions A consideration of equity in the development and implementation of clinical practice guidelines and quality assessments of the evidence would achieve more in the participation of potential actors in the process and reflect on the effectiveness of the proposed interventions across all social groups.